Vogel's qualitative inorganic analysis - Svehla, G.; Sivasankar, B. (Chennai; Pearson, 2012)
Vogels Qualitative Inorganic Analysis (in its seventh edition) follows the current trends and techniques in the field of analytical chemistry. Written for undergraduate and postgraduate students of chemistry, this revised and updated edition treats each concept and principle systematically to make the subject comprehensible to beginners as well as advanced learners.
Appendix 336-355p.; Index 356-372p.
Keywords: Experimental techniques; Reactions of thr anions; Chemistry